Overlapping and unique signatures in the proteomic and transcriptomic responses of the nematode Caenorhabditis elegans toward pathogenic Bacillus thuringiensis. Issue 1 (July 2015) - Yang, Wentao; Dierking, Katja; Esser, Daniela; Tholey, Andreas; Leippe, Matthias; Rosenstiel, Philip; Schulenburg, Hinrich
Highlights We compared the pathogen-induced transcriptome and proteome of C. elegans. A strong overlap was identified for various gene groups, especially C-type lectin genes. A unique proteome signature additionally indicated regulation beyond transcription. The post-transcriptional effects are likely controlled by AMP-activated protein kinases.